Oleoyl-lysophosphatidylinositol enhances glucagon-like peptide-1 secretion from enteroendocrine L-cells through GPR119 - Ahmad Arifin, Syamsul; Paternoster, Silvano; Carlessi, Rodrigo; Casari, Ilaria; Ekberge, Jeppe Hvidtfeldt; Maffucci, Tania; Newsholme, Philip; Rosenkilde, Mette M.; Falasca, Marco (Elsevier, 2018)
The gastrointestinal tract is increasingly viewed as critical in controlling glucose metabolism, because of its role in secreting multiple glucoregulatory hormones, such as glucagon like peptide-1 (GLP-1). Here we investigate the molecular pathways behind the GLP-1- and insulin-secreting capabilities of a novel GPR119 agonist, Oleoyl-lysophosphatidylinositol (Oleoyl-LPI). Oleoyl-LPI is the only LPI species able to potently stimulate the release of GLP-1 in vitro, from murine and human L-cells, and ex-vivo from murine colonic primary cell preparations. Here we show that Oleoyl-LPI mediates GLP-1 secretion through GPR119 as this activity is ablated in cells lacking GPR119 and in colonic primary cell preparation from GPR119-/- mice. Similarly, Oleoyl-LPI-mediated insulin secretion is impaired in islets isolated from GPR119-/- mice. On the other hand, GLP-1 secretion is not impaired in cells lacking GPR55 in vitro or in colonic primary cell preparation from GPR55-/- mice. We therefore conclude that GPR119 is the Oleoyl-LPI receptor, upstream of ERK1/2 and cAMP/PKA/CREB pathways, where primarily ERK1/2 is required for GLP-1 secretion, while CREB activation appears dispensable